Urgensi Pembaharuan Acara Hukum Pidana Terkait Alat Bukti Elektronik dalam Perspektif Tujuan Hukum - Felen Felen; Nabila Fitria Almadea (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Globalization affects the development of technology that facilitates human activities, but also presents a threat in the form of cyber crime. Cyber crime utilizes computers and the internet as its main tools. However, KUHAP has not fully regulated the validity of electronic evidence which is vital in handling cyber crime cases. This lack of clarity will not provide justice, benefit, and legal certainty to the community, as the purpose of the law itself should be. Therefore, the discussion of the validity of electronic evidence is important, considering its influence in deciding a case. With the alignment of das sein and das sollen, it is hoped that the real purpose of law will be achieved. This research highlights the urgency of legal reform along with technological developments in order to reduce the reduction of legal objectives and realize dynamic positive law in Indonesia. This type of research is normative juridical research or normative legal research. The results of the research are expected to contribute to the development of relevant laws.